Bimbingan Belajar Dalam Meningkatkan Motivasi Belajar Anak Sekolah Dasar Di Desa Ciklapa Tahun 2022 - Raditya Pratama; Rama Cipta Prasetya; Ngabdullah Ali (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
Thematic Real Work Lectures (KKN) are KKN whose activity programs focus on certain areas according to social problems and the direction of development policies implemented by certain regional governments. STKIP Darussalam Cilacap organizes a Real Work Lecture program using the thematic method. KKN-T is intended to develop a spirit of empathy and concern for problems that occur in society. This tutoring work program is carried out using the AKSI learning method, namely active, creative, relaxed and innovative. The Tutoring work program for elementary school children in Ciklapa Village, Kedungreja District has been implemented well and smoothly. This tutoring program was carried out in collaboration between the person in charge, KKN students, and the community around the KKN-T STKIP Darussalam Cilacap post. This tutoring program was implemented successfully as seen from the enthusiasm and interest of the elementary school children who took part in this tutoring program.